Effects of Malaysian strains of Toxoplasma gondii on dopamine and kynurenic acid genes and their possible risk in schizophrenia-like rat model - Wana, Mohammed Nasiru (2020)
Schizophrenia is a complex brain disorder that is the cause of neuropathological changes with an unknown source. The pathological condition associated with the schizophrenic individual is the brain of the infected host that results into changes associated with the neurotransmitters. Neuropathological and epidemiological data have also shown that some causes of schizophrenia may be strongly related to environmental agents, such as exposure to infectious microorganism. The protozoan parasite Toxoplasma gondii (T. gondii) have been reported in the brain of rodents and also diagnosed in the schizophrenic individual which is implicated as the cause of behaviour deficits. The present study collected faeces of free-roaming cats (FRC) and pet cats (PC) in Klang Valley, Malaysia to detect and genotype T. gondii and further tested their effects on rats’ behaviour. Wistar albino rats were injected subcutaneously with MK-801 (dizocilpine) 0.6 mg/kg twice a day for seven days before the commencement of the behaviour test to established rat model of schizophrenia. Three experimental groups of rats were inoculated from a single strain of type I, type II and type III respectively, while another group was inoculated with phosphate buffered saline (PBS) as control. Rats were tested serologically two weeks post infection (pi) to confirmed acute T. gondii infection. Behavioral assessment of open field test (OFT), fatal feline attraction test (FFAT) and elevated plus maze (EPM) were evaluated at nine weeks pi, while another behavioural test of Morris water maze (MWM) was carried out at 10 and 11 weeks pi. Subsequently, at the end of the behavioral test, rats were euthanized and whole brain assessed for T. gondii tissue cysts distribution using haematoxylin and eosin staining. Additionally, molecular analysis of a neurotransmitter gene expression of dopamine (dopamine receptor; DRD) and kynurenic acid (indoleamine-2, 3 dioxygenase; IDO) genes were evaluated. Overall, the results revealed 17 (8.5%) were T. gondii positive samples in both FRC and PC in Malaysia within the study area. More T. gondii positive faecal samples were found in FRC 13 (13.0%) compared with PC 4 (4.0%). Four T. gondii genotype strain of type I, II, III and mixed infection were identified as clonal with genotype type I as the predominant. The result of the serological test of toxoplasma-IgM found at least six or more experimental rats in T. gondii infected groups were positive, while the control group of rat inoculated with PBS and MK-801 (model of schizophrenia) administered group of the rat were negative. The infected rats present with increased in locomotor activity, less aversion to cat urine scented areas, decrease anxiety, and poor memory retention. The results of the haematoxylin and eosin histological staining of the T. gondii infected rat brain coronal section revealed tissue cysts distribution. T. gondii tissue cysts were found in some of the major brain domain without tropism to a particular area. The present study on the brain gene expression of T. gondii infected rats indicated changes associated with the dopamine receptors (DRD) and indoleamine-2,3-dioxygenase (IDO). There is a reduction in the level of DRD which is involved in the dopamine pathway, while the level of IDO was elevated which is part of the kynurenic acid pathway. Further, the behavioural test coupled with DRD and IDO abnormalities support the data of cognitive deficits in T. gondii infected rats, while the effect of type I, type II and type III were comparable. Therefore these findings suggest that Malaysian species of T. gondii are implicated in some causes of behaviour changes that are responsible for schizophrenic conditions.